The Influence of Social Media on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Tangerang Regency in an Effort to Penetrate the Global Market - Purwaningsih, Nining; Wiliana, Eneng (PT Mattawang Mediatama Solution, 2024)
The purpose of this study is to analyze and analyze the influence of social media use on the performance of MSMEs in Tangerang Regency in an effort to penetrate the global market. The research uses a quantitative approach with the type of explanatory research. The research sample is 100 MSMEs selected using the purposive sampling technique. Data analysis using Partial Least Square (PLS) with SmartPLS software. Social media has a positive and significant effect on the performance of MSME actors, Social Media has a positive and significant effect on the global market, MSME performance has no effect on the global market and Social media has no effect on the performance of MSMEs through the Global Market. There are many limitations in conducting this research, many difficulties in determining respondents who have or have not done the global market in their business. Respondents are limited in using social media because there are still respondents who only use 1 or 2 social media. Therefore, this research is still not optimal, and it is difficult to reach respondents who are not members of the MSME group. This research hopes that MSME business actors can improve their performance and can strive to penetrate the global market in the business sector in order to increase profits and MSME performance by better understanding the use of social media. The results of the study show that social media has an impact on the performance of MSMEs.